Dictionary of Qumran Aramaic - Cook, Edward M. 1952- (Winona Lake Eisenbrauns, 2015)
Intro -- Contents -- Introduction -- Acknowledgments -- Abbreviations -- א -- ב -- ג -- ד -- ה -- ו -- ז -- ח -- ט -- י -- כ -- ל -- מ -- נ -- ס -- ע -- פ -- צ -- ק -- ר -- שׁ -- שׂ -- ת -- Bibliography of Works Cited.
Description based upon print version of record
Keywords: Aramaic language ; Dialects ; West Bank ; Qumran Site ; Dictionaries; Aramaic language ; Dictionaries ; English; Electronic books; Electronic books